DD's Supermarket a total systems study - Abibuag, Angeline; Dela Cruz, Darlene Grace; Simbulan, Dennyver; Telewik, Jeminah Grace (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
DD's Supermarket Corporation (DD's) is a domestic corporation that engages in the wholesale and retail of consumer goods, particularly grocery items, and has been in the business for 16 years in the town center of Apalit, Pampanga. DD's is able to serve different kinds of customers yearly amounting to gross revenue of more than Php 100 million. However, the emergence of competitors like Red Camia (which is just several meters away from DD's), Puregold Jr., and Savemore brought about relevant changes in DD's market share. Surveys were conducted in order to characterize the customers of DD's Supermarket. Half of DD's surveyed customers conveyed they had problems encountered during their shopping. Sixty- four percent (64%) of these customers reported dissatisfaction in the check-out counters' waiting time and 24% in the usual incidence of stock-outs of their needed items and supplies. This compels them to shop at another nearby supermarket, which creates sales opportunity losses to DD's Supermarket. To aid the proponents in the analysis of the problem of long queues, the current queuing system is modeled using the simulation tool software, ProModel, and the data gathered from the time study. Upon evaluating all the proposed alternatives for the solution, it was concluded that the company should consider the option of revising the counter shifting schedules corresponding to the recorded peak hours. If implemented, DD's can expect a reduction to their counters' average waiting time by about 84.6%. On the other hand, a stock out solution matrix was created to serve as the basis of actions in solving the stock out problem. This matrix classifies products according to whether or not they are fast moving and whether or not they are products that experience stock outs. In addition, a plan of action was also suggested to strengthen the relationship of the company with the suppliers. Other concerns or problems encountered by the customers of the supermarket include unclear and mismatched price tags in the shelves with the actual price in the database, unreadable aisle signage and unfamiliar arrangement of products. Several proposals have also been formulated and evaluated to address these problems.
Submitted in partial fulfillment of the course requirements in IE 155 : Total systems study.
Keywords: Supermarkets -- Philippines; System analysis